2017
DOI: 10.1017/jfm.2017.410
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the turbulence induced by a bubble swarm rising within incident turbulence

Abstract: This work reports an experimental characterisation of the flow properties in a homogeneous bubble swarm rising at high Reynolds numbers within a homogeneous and isotropic turbulent flow. Both the gas volume fraction alpha and the velocity fluctuations u '(0) of the carrier flow before bubble injection are varied, respectively, in the ranges 0% < alpha < 0.93% and 2.3 cm s(-1) < u '(0) < 5.5 cm s(-1). The so-called bubblance parameter (b = V-r(2)alpha/u '(2)(0) 0, where V-r is the bubble relative rise velocity)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 31 publications
(58 reference statements)
8
85
1
Order By: Relevance
“…, we find that w is indeed comparable to the viscous dissipation in the fluid phase µ,f (see table 1). (Riboux et al 2010;Almras et al 2017;Prakash et al 2016). Our results are consistent with the recently proposed stochastic model of Risso (2016) and the turbulent agitation because of flow instabilities together lead to the observed velocity distributions.…”
Section: Bubble Suspension and Kinetic Energy Budgetsupporting
confidence: 91%
See 1 more Smart Citation
“…, we find that w is indeed comparable to the viscous dissipation in the fluid phase µ,f (see table 1). (Riboux et al 2010;Almras et al 2017;Prakash et al 2016). Our results are consistent with the recently proposed stochastic model of Risso (2016) and the turbulent agitation because of flow instabilities together lead to the observed velocity distributions.…”
Section: Bubble Suspension and Kinetic Energy Budgetsupporting
confidence: 91%
“…Riboux et al (2010) investigated turbulence in the wake of a bubble swarm and found the k −3 scaling for length scales larger than the bubble diameter d (i.e., k < 2π/d), whereas Mercado et al (2010); Prakash et al (2016) observed this scaling for scales smaller than d in a steady state bubble suspension. Experiments on bouyancy driven bubbly flows in presence of grid-turbulence (Lance & Bataille 1991;Prakash et al 2016;Almras et al 2017) observe Kolmogorov scaling for scales larger than the bubble diameter and smaller than the forcing scale and a much steeper k −3 scaling for scales smaller than the bubble diameter and larger than the dissipation scale. Lance & Bataille (1991) argued that, assuming production because of wakes to be local in spectral space, balance of production with viscous dissipation leads to the observed k −3 scaling.…”
Section: Introductionmentioning
confidence: 99%
“…These have been characterised by looking at the statistical properties of the liquid phase in the absence of bubbles (see Ref. [28] for more details). Table I summarises the flow characterisation of the eight single phase turbulence cases investigated in the present study.…”
Section: Experimental Set-up and Instrumentationmentioning
confidence: 99%
“…We expect this to be comparable to the Lagrangian integral time scale, which is relevant for turbulent mixing [32]. A homogeneous bubble swarm is produced using 621 capillary tubes of inner diameter 0.12 mm positioned on 9 islands, which are located below the active-grid [28]. By varying the gas flow rate, the gas volume fraction α can be adjusted from 0 to 0.93%.…”
Section: Experimental Set-up and Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation